Assessment of the Antidiabetic and Antihyperlipidemic Effects of Aqueous Extract from Zanthoxylum armatum DC. in High-Fat Diet and Streptozotocin-Induced Type 2 Diabetic Rats - Kesavan, Keerthana; Gnanasekaran, Jothi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Diabetes mellitus refers to a collection of metabolic illnesses that are distinguished by elevated levels of sugar in the blood. This occurs due to inadequate synthesis of insulin, impaired functioning of insulin, or a combination of both factors. Owing to inactive lifestyles and little knowledge about the illness, it has emerged as a noteworthy socioeconomic concern. India has a wealth of historical knowledge in the field of natural medicine. Zanthoxylum armatum DC., a plant with a long history of usage in Indian medicine, is the subject of this study. This research sought to investigate whether or not a water-based extract of Zanthoxylum armatum DC. had any antidiabetic benefits in Wistar albino rats that had been streptozotocin high-fat diet-induced diabetics. Both those with normal glucose tolerance and those tested for glucose tolerance showed a drop in blood glucose levels after a glucose load. Insulin sensitivity was also shown to be higher in the insulin tolerance test. Blood glucose, triglyceride, total cholesterol, and free fatty acid levels were significantly reduced after 45 days of therapy with the water-based extract of Z. armatum DC. Furthermore, there was a documented rise in plasma insulin and liver glycogen concentrations. These findings indicate that the selected plant has properties that may help manage diabetes and reduce high levels of lipids in the blood.